The Impact of Trade Openness on Sustainable Development: Study Case on G20 Group Countries - Fathya Dhiya Ulhaq,; Widyastutik,; Deniey A. Purwanto, (Journal of Social Transformation and Regional Development, 2023)
The issues concerning environmental damage, poverty, and unequal income distribution have taken center stage in contemporary policies aimed at sustainable development. Amidst various policy measures, trade policies continue to hold a prominent position due to their direct and indirect connections with sustainable development. It is widely believed that trade openness can incentivize both production and consumption. However, the rapid economic integration resulting from trade openness can also have adverse effects on society, employment, and the environment. Therefore, the primary objective of this study is to examine the impact of trade openness and other relevant factors on sustainable development in the G20 countries. This research adopts a quantitative approach, utilizing secondary data. Data analysis is conducted using a Heterogeneous Dynamic Panel econometric method, covering the period from 1990 to 2019. The findings of this study reveal that in the short term, sustainable development in the G20 countries is positively and significantly influenced by capital formation and environmental quality. Conversely, in the long run, sustainable development is positively and significantly affected by trade openness. Consequently, the recommendation stemming from this research for G20 countries is to further develop trade policies that prioritize and support sustainable development goals.